(untitled) (International Journal of Nursing Education, 2021)
COVID-19 is an infectious disease caused by the coronavirus, SARS-CoV-2. The spread of several types ofdiseases, including COVID-19, is influenced by location or spatial factor. The purpose of this research wasto examine the spatial relationship among the spread of COVID-19 in Indonesia. Secondary data is usedfrom the Indonesian Ministry of Health website. The data analyzed was the cumulative number of positivecases of COVID-19 in Indonesia until October 19th, 2020. Spatial Autocorrelation, Moran’s Index, andLocal indicators of spatial association (LISA) were used to examine these relationships. Geoda softwarewas used in performing spatial statistical analysis. The spread of the cumulative number of COVID-19cases in Indonesia is spatially related, with a Moran’s Index value of 0.251. Four provinces have significantLISA scores, namely South Sumatra, Banten, West Java, and South Sulawesi. South Sumatera is relativelysafe since it is located in the an area with relatively low COVID-19 cases. West Java is perilouse with highCOVID-19 cases and surrounded by an area with a high number of cases. Banten needs to be vigilant ofthe high number of cases’ possibility since the surrounded area can be the main influence. South Sulawesihas a very high number of COVID-19 cases, which can be the new source of infection for the surroundingareas. The Indonesian government needs to act on a regulation in order to decrease COVID-19 distributionby limiting people’s commute between provinces.